Real‐Time Quantification of Cell Internalization Kinetics by Functionalized Bioluminescent Nanoprobes. Issue 39 (12th August 2019) - Wu, Di; Yang, Yilong; Xu, Pengcheng; Xu, Duo; Liu, Yang; Castillo, Roxanne; Yan, Ran; Ren, Jie; Zhou, George; Liu, Chaoyong; Qin, Meng; Du, Juanjuan; et al.
Abstract: Cells transport mass dynamically, crossing cell membranes to maintain metabolism and systemic homeostasis, through which biomolecules are also delivered to cells for gene editing, cell reprograming, therapy, and other purposes. Quantifying the translocation kinetics is fundamentally and clinically essential, but remains limited by fluorescence‐based technologies, which are semi‐quantitative and only provide kinetics information at cellular level or in discrete time. Herein, a real‐time method of quantifying cell internalization kinetics is reported using functionalized firefly‐luciferase nanocapsules as the probe. This quantitative assay will facilitate the rational design of delivery vectors and enable high‐throughput screening of peptides and other functional molecules, constituting an effective tool for broad applications, including drug development and cancer therapy. Abstract : A real‐time method of quantifying cell internalization kinetics is developed using functionalized firefly‐luciferase nanocapsules as the probe, which is an effective tool for the study of cell internalization, drug development, and cancer therapy.